2016
DOI: 10.3390/atmos7050070
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Optical Properties Based on Ground and Satellite Retrievals during a Serious Haze Episode in December 2015 over Beijing

Abstract: An extreme haze event occurred in the Beijing area from 17 to 23 December 2015. Ground-based measurements and satellite observations during this event were used to further our understanding of the formation process of haze pollution and aerosol optical properties. The results suggest that high relative humidity, poor diffusion conditions (low wind speed and stable stratification) and favorable secondary transformation conditions under the hygroscopic growth of aerosol and high emissions led to this serious haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…It is worth noting that, in addition to the increased explained proportion of SO 2 and BC, among these meteorological factors, the role of diffusion-related parameters (such as horizontal and vertical wind speed, representing horizontal and vertical diffusion, respectively) seems to be the most prominent. This is consistent with the findings of Gui et al (2019), who found wind speed to be the dominant meteorological driver for decadal changes in fine particulate matter over SC, based on a 19-year record of satellite-retrieved fine particulate matter data (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016).…”
Section: Relative Contributions Of Local Emissions and Meteorologicalsupporting
confidence: 93%
See 1 more Smart Citation
“…It is worth noting that, in addition to the increased explained proportion of SO 2 and BC, among these meteorological factors, the role of diffusion-related parameters (such as horizontal and vertical wind speed, representing horizontal and vertical diffusion, respectively) seems to be the most prominent. This is consistent with the findings of Gui et al (2019), who found wind speed to be the dominant meteorological driver for decadal changes in fine particulate matter over SC, based on a 19-year record of satellite-retrieved fine particulate matter data (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016).…”
Section: Relative Contributions Of Local Emissions and Meteorologicalsupporting
confidence: 93%
“…For example, using the long-term and high-quality AOD datasets from the Aerosol Robotic Network (AERONET), found that North America and Europe experienced a uniform decrease in AOD from 2000 to 2013. Che et al (2015) estimated the change in AOD based on AOD data at 12 long-term ground-based sites in China from the China Aerosol Remote Sensing Network (CARSNET) and found that AOD showed a downward trend from 2006 to 2009 and an upward trend from 2009 to 2013. Compared with the spatial sparseness of ground-based observations, inferences from satellite-based sensors can provide a global perspective of AOD change, due to their continuous spatial measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols are solid particles or suspended liquids in the atmosphere that are the result of natural activities [1,2], burning fuels [3,4], and human activities [5,6]. In recent years, atmospheric aerosols have had a major impact on human health [7], ecosystems [8] and geochemical cycles [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, as a result of a remarkable increase in the emissions of primary pollutants caused by the rapid development of China's economy and urbanization, China has frequently suffered from persistent and severe haze events with high concentration of pollutants, which has aroused considerable concern of the society [1][2][3][4][5]. A high loading (or concentration) of aerosol particles concentration during haze days can reduce visibility through directly scattering and absorbing the incident light, which has potentially impact on road traffic and air transportation [6][7][8]. Furthermore, numerous studies have shown that, as a result of the intensification of air pollution (especially fine particulate matter pollution), some potential health risks have been induced, including respiratory 1c), and unfavorable meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%